Antioxidant and lipase inhibitory activities of Camellia pollen extracts: the effect of composition and extraction solvents. Issue 1 (31st December 2022) - Yang, Yuanfan; Zhou, Cunshan; Ma, Haile; Dong, Yating; Fu, Jiayu; Lai, Xiaoyan; Yagoub, Abu El-Gasim A.; Peng, Wenjun; Ni, Hui
ABSTRACT: This work evaluated the potential of Camellia pollen extracts as an antioxidant and lipase activity inhibitor from the pollen composition and the extraction solvent. The lipase inhibitory activity, the scavenging radical's ability (ABTS and DPPH) and the ferric-reducing ability of the seven extracts were examined. The fatty acid profile of the extracts with excellent antioxidant and lipase inhibitory activity was also determined by GC-MS. The ethyl acetate (IC50  = 2.07 ± 0.20 mg/mL) and the acetone extracts (IC50  = 1.19 ± 0.07 mg/mL) showed better lipase inhibitory activity. For the antioxidant activity, the methanol (IC50  = 2.55 ± 0.34 mg/mL), ethanol (IC50  = 2.87 ± 0.23 mg/mL) and the water (IC50  = 2.62 ± 0.05 mg/mL) extracts had superior ABTS radical-scavenging ability. Greater DPPH radical-scavenging ability was seen in the ethanol (IC50  = 2.92 ± 0.04 mg/mL) and acetone extracts (IC50  = 3.09 ± 0.12 mg/mL). The ethyl acetate and petroleum ether extracts manifested better FRAP. The fatty acid composition of the methanol and ethyl acetate extracts belonged to the unsaturated fatty acids. This study indicated that the lipase inhibitory activity and the antioxidant activity found in Camellia pollen may exert dual benefits for preventing and treating obesity.